A system dynamics model of tellurium availability for CdTe PV - Houari,Y; Speirs,J; Candelise,C; Gross,R (Progress in Photovoltaics: Research and Applications, 2013)
The routine availability of key component materials has been highlighted as a potential constraint to both extensive deployment and reduction in production costs of thin-film photovoltaic (PV) technologies. This paper examines the effect of material availability on the maximum potential growth of thin-film PV by 2050 using the case of tellurium (Te) in cadmium telluride (CdTe) PV, currently the dominating thin-film technology with the lowest manufacturing cost. The use of system dynamics (SD) modelling allows for a dynamic treatment of key Te supply features and prospects for reductions in PV demand via material efficiency improvements, as well as greater transparency and a better understanding of future recycling potential. The model's projections for maximum Te-constrained CdTe PV growth by 2050 are shown to be higher than a number of previous studies using static assumptions—suggesting that a dynamic treatment of the resource constraints for CdTe inherently improves the outlook for future deployment of this technology. In addition, the sensitivity analysis highlights certain complex correlations between the maximum potential CdTe growth by 2050 and the rated lifetime of PV modules as well as the reported size of global Te resources. The highest observed sensitivities are to the recovery rate of Te from copper anode slimes, the active layer thickness, the module efficiency and the utilisation rate of Te during manufacturing, all of which are highlighted as topics for further research. Copyright © 2013 John Wiley & Sons, Ltd.